Intestinal occlusion due to chronic appendicitis - Santos Dubra, Alfonso (Cirugía del Uruguay, 1972)
A high number of cases of acute appendicitis n:ay .cool off completely through med.ical treatment. But recent statistics show that in the same manner as ,acute operated appendicitis may be complicated by intestinal occlusion, so can cases where no surgery has been performed and this complication may appear a 1ong time ¡¡fter the acute accident. Two cases responéling to this latter characterist.ic are discussed. The occlusive picture appeared 5 and :3 years after the acute picture, as a consequence of a lopped around the inflamatory focus. The formation and development of the pathological process is discussed, including its clinical sequence. Existing dificulties in determining the ethiological cause of the occlusive picture are analyzed, but the authors point out that a good anamnesis may put the physician in the right track towards its determination. 'I'he use of antibiotics may rapidly reduce the inflamatory process, but the organ does not become normal and there. is a sequella of adhesions and kinks, etc., which constitute a permanente threat to the patient's l!ve. For ali the abovementioned reasons it is considered that early surgery is safer than conservative treatment, and thus it becomes the ideal procedure.